Deciphering the Iron Side of Stroke: Neurodegeneration at the Crossroads Between Iron Dyshomeostasis, Excitotoxicity, and Ferroptosis - DeGregorio-Rocasolano, Núria; Martí-Sistac, Octavi; Gasull, Teresa (Frontiers in Neuroscience, 2019)
Iron represents a double-edge sword in metabolism in general in most tissues, and especially in the brain. Whereas the high metabolic demands of brain cells require iron as a redox-active metal for ATP-producing enzymes, the brain is highly vulnerable to the devastating consequences of excessive iron-induced oxidative stress and, as recently found, to ferroptosis as well. The blood-brain barrier (BBB) shelters the brain from fluctuations of systemic iron. Under pathological conditions, and especially in acute brain pathologies such stroke, the BBB is disrupted and iron pools from blood gain sudden access to brain parenchyma, being crucial in mediating stroke-induced neurodegeneration. Each brain cell type reacts with changes in their expression of proteins involved in iron uptake, efflux, storage and mobilization to preserve its internal iron homeostasis, with specific organelles such as mitochondria showing specialized responses. However, during ischemia, neurons are challenged with excess extracellular glutamate in the presence of high levels of extracellular iron; this causes glutamate receptor overactivation that boosts neuronal iron uptake and a subsequent overproduction of membrane peroxides. This glutamate-driven neuronal death can be attenuated by iron-chelating compounds or free radical scavenger molecules. Moreover, vascular wall rupture in haemorrhagic stroke results in accumulation and lysis of iron-rich red blood cells at the brain parenchyma, and the subsequent presence of hemoglobin and iron-heme at the extracellular milieu, thus contributing to iron-induced lipid peroxidation and cell death. This review summarizes recent progress made in understanding the ferroptosis component underlaying both ischemic and hemorrhagic stroke subtypes.